Sarcopenia is as common in older patients with dementia with Lewy bodies as it is in those with Alzheimer's disease. Issue 5 (3rd April 2022) - Dost, Fatma Sena; Ates Bulut, Esra; Dokuzlar, Ozge; Kaya, Derya; Mutlay, Feyza; Yesil Gurel, Besra Hazal; Isik, Ahmet Turan
Abstract : Aim: Alzheimer's disease (AD) and dementia with Lewy body (DLB) constitute the most common types of dementia, and are two common geriatric syndromes; however, sarcopenia has not been elaborately evaluated in DLB so far. Therefore, this study aimed to investigate the relationship between sarcopenia and DLB in older adults. Methods: In this retrospective and cross‐sectional study, 662 participants, who were followed in a memory clinic at the Geriatrics department of a university hospital, were included. Comprehensive Geriatric Assessment, including the activities of daily living, malnutrition and malnutrition risk, frailty, cognition, and sarcopenia were assessed. Sarcopenia was defined according to the revised European Working Group on Sarcopenia in Older People‐2 criteria. Results: A total of 662 participants (461 healthy controls, 133 with AD and 68 with DLB) with a mean age of 73.60 ± 7.50 years were included. The prevalence of probable sarcopenia and sarcopenia was 53.4% and 19.5%, respectively, in patients with AD, whereas it was 55.9% and 19.1%, respectively, in patients with DLB. After adjustment analyses, probable sarcopenia, sarcopenia and low muscle mass were related to AD ( P < 0.001, P = 0.001, P < 0.001, respectively). Probable sarcopenia and slow gait speed were associated with DLB ( P < 0.01, P < 0.001, respectively). Conclusions: Sarcopenia is common in patients with DLB and in those with AD, and seems to be closely related to low muscle strength and slow gait speed in DLB patients. Considering sarcopenia‐related negative health outcomes in older adults, the evaluation of sarcopenia, therefore, should also be among the follow‐up and treatment goals of DLB patients. Geriatr Gerontol Int 2022; 22: 418–424 .